2021
DOI: 10.1186/s12957-021-02381-5
|View full text |Cite
|
Sign up to set email alerts
|

Decreased exosome-delivered miR-486-5p is responsible for the peritoneal metastasis of gastric cancer cells by promoting EMT progress

Abstract: Background The present study aims to investigate the preliminary mechanism underlying the peritoneal metastasis of gastric cancer cells. Methods Exosomes from GC9811 cells (Con-Exo) and from GC9811-P cells (PM-Exo) were extracted by ultracentrifugation, which were identified with transmission electron microscopy (TEM) and nanoparticle trafficking analysis, as well as the expression of CD9, CD63, and CD81 detected by Western blot assay. α-SMA expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…We hypothesized that α-hederin might regulate A549T-derived sEVs cargos involved in TGFβ/SMADs and SREBF1/FASN signaling. A variety of non-coding RNAs, including microRNAs (miR-21-5p, miR-23a-3p, miR-125b-5p, miR-145-5p, miR-26a-5p, miR-6766-3p, miR-671-5p, let-7a-5p, miR-486-5p, miR-29c-3p, and miR-29c-5p) and long non-coding RNAs (lncRNA ZEB1-AS1, LINC00960, LINC02470, lncRNA SOX2-OT, and lncRNA CDKN2B-AS1), were shown to be sorted into sEVs or exosomes and directly targeted regulatory genes in the TGFβ/SMADs pathway ( Solé et al, 2015 ; Fang et al, 2016 ; Hu et al, 2019a ; Huang et al, 2020 ; Wang et al, 2021b ; Chen et al, 2021 ; Wang et al, 2021c ; Lin et al, 2021 ; Wu et al, 2021 ; Zhou et al, 2021 ; Wu et al, 2022a ; Luo et al, 2022 ). Among these non-coding RNAs, we observed that miR-21-5p, miR-23a-3p, and miR-125b-5p decreased after treatment with A549T-derived sEVs and increased after further treatment with α-hederin ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that α-hederin might regulate A549T-derived sEVs cargos involved in TGFβ/SMADs and SREBF1/FASN signaling. A variety of non-coding RNAs, including microRNAs (miR-21-5p, miR-23a-3p, miR-125b-5p, miR-145-5p, miR-26a-5p, miR-6766-3p, miR-671-5p, let-7a-5p, miR-486-5p, miR-29c-3p, and miR-29c-5p) and long non-coding RNAs (lncRNA ZEB1-AS1, LINC00960, LINC02470, lncRNA SOX2-OT, and lncRNA CDKN2B-AS1), were shown to be sorted into sEVs or exosomes and directly targeted regulatory genes in the TGFβ/SMADs pathway ( Solé et al, 2015 ; Fang et al, 2016 ; Hu et al, 2019a ; Huang et al, 2020 ; Wang et al, 2021b ; Chen et al, 2021 ; Wang et al, 2021c ; Lin et al, 2021 ; Wu et al, 2021 ; Zhou et al, 2021 ; Wu et al, 2022a ; Luo et al, 2022 ). Among these non-coding RNAs, we observed that miR-21-5p, miR-23a-3p, and miR-125b-5p decreased after treatment with A549T-derived sEVs and increased after further treatment with α-hederin ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…Liao et al confirmed that HDAC5 was highly expressed in GC tumor tissues and promoted the proliferation and migration capability of GC cells [ 30 ]. Moreover, Lin et al showed that HDAC5 was upregulated in GC cells and boosted the invasiveness of GC cells by enhancing matrix metalloproteinase 9 (MMP9) [ 31 ]. MMP9 has been confirmed as an important gene implicated in tumor invasion and metastasis through epithelial-mesenchymal transition (EMT) processes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…When GC cells were co-cultured with EVs rich in GKN1, the expression of E-cadherin in GC cells increased, while the expression of proteins such as N-cadherin significantly decreased, suggesting that GKN1 derived from EVs inhibited GC metastasis by suppressing EMT ( Yoon et al, 2020 ). Studies have also shown that biologically active substances such as miR-486-5p and circ-ITCH delivered by EVs could inhibit the metastasis of GC by suppressing EMT ( Wang et al, 2021b ; Lin et al, 2021 ).…”
Section: Evs Affect the Metastasis Of Gc Through Emt And Mmtmentioning
confidence: 99%